PENGEMBANGAN ALAT UNGKAP MASALAH - Kartika Hajati (Perspektif Ilmu Pendidikan, 2008)
This empirical study on the quality of guidance and consoling instrument (AUM U2) aims at this closing the validity and reliability of the instrument use in government high school in is Jakarta. This study is also expected will be able to give contribution in improving the instrument to be a standard instrument. The finding shows that although the instrument (AUM U2) has a good validity and reliability, same weakness still have to be tackled, for which this study provide some recommendation.